Phenanthroline polyazamacrocycles as G-quadruplex DNA binders. Issue 15 (3rd April 2018) - Carvalho, Josué; Quintela, Telma; Gueddouda, Nassima M.; Bourdoncle, Anne; Mergny, Jean-Louis; Salgado, Gilmar F.; Queiroz, João A.; Cruz, Carla
Abstract : Several phenanthroline polyazamacrocycles are proposed as ligands for c-MYC and telomeric G-quadruplex structures. Abstract : Targeting quadruplex DNA structures with small molecules is a promising strategy for anti-cancer drug design. Four phenanthroline polyazamacrocycles were studied for their binding affinity, thermal stabilization, inhibitory effect on the activity of helicase towards human telomeric 22AG and oncogene promoter c-MYC G-quadruplexes (G4s), and their ability to inhibit Taq polymerase-mediated DNA extension. The fluorescence resonance energy transfer (FRET) melting assay indicates that the melting temperature increases (Δ T m values) of c-MYC and 22AG G4s are 17.2 and 20.3 °C, respectively, for the ligand [32]phen2 N4 followed by [16]phenN4 (11.3 and 15.0 °C, for c-MYC and 22AG, respectively). Competitive FRET assays show that [32]phen2 N4 and [16]phenN4 exhibit G4 selectivity over duplex DNA. Different G4s were compared; no considerable selectivity of the ligands for a specific G4 was found. Circular dichroism (CD) confirms the formation of G4 structures and the melting experiments show that [16]phenN4 and [32]phen2 N4 are the most stabilizing ligands with a Δ T m of 19.3 °C and 15.1 °C, respectively, at 5 molar equivalents for the c-MYC G4. The fluorescent intercalator displacement (FID) assay also demonstrates that ligand [32]phen2 N4 furnishes very low DC50 values (0.87–1.24 μM), indicating high stabilization of c-MYC and 22AG G4s. These results suggest that the hexyl chain in these compounds plays an important role in regulating the stabilization of these G4s. Binding constants, determined by fluorescence titrations, indicate a moderate ligand–G4 binding with K SV between 105 and 10 6 M −1 in which [16]phenN4 has a slightly higher apparent binding constant for telomeric 22AG G4 than that for the c-MYC G4. The ligand's ability to inhibit Taq polymerase confirms the biological activity of [16]phenN4 and [32]phen2 N4 against the c-MYC G4. In addition, ligands [32]phen2 N4 and [16]phenN4 affect the unwinding activity of Pif1 in the presence of DNA systems harboring c-MYC and telomeric G4 motifs.